Cannabis-Induced Mania - Habil, Mohd Hussain (Faculty of Medicine, University of Malaya, 1999)
Hypomanic episodes have been reported in two patients who were known to have abused cannabis. The nature of its presentation, possible association and treatment modalities are discussed herewith. A greater awareness of such a condition can put clinicians in a better position to give appropriate treatment immediately, and thus prevent any kind of re-occurrence of such a condition especially in vulnerable patients.